Podatek od zysków wojennych w polskim systemie danin jako źródło finansowania kosztów wojny polsko-bolszewickiej - Antonów, Dobrosława (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The paper draws attention to one of the emergency taxes in the history of the Polish Treasury, i.e. a tax on war profits. It was levied under the Decree of 5 February 1919 on the Establishment of a Tax on War Profits. This levy introduced a concept which was developed in Europe and built on the First World War experience. In the reborn Poland, the tax was supposed to have two functions: fiscal — as a source of financing the extraordinary expenditure arising from the war against the Soviets and a social function — as an additional burden on those taxpayers who were able to accumulate wealth and earn substantial profits as a result of the First World War.
Keywords: podatek; podatek od zysków wojennych; wojna; podatek nadzwyczajny; wojna polsko-bolszewicka; pierwsza wojna światowa; koszty wojny; gospodarka wojenna; wydatki publiczne; odrodzona Polska; okres międzywojenny; podatki w okresie międzywojennym; historia skarbu państwa polskiego; wojna z Sowietami